The Effect of IAA Concentration and Growing Media Composition on Banana Raja Bulu (Musa paradisiaca L.) Planlet Growth at Aclimatization Stage - Andariza, Isna Panca; Kusmiyati, Florentina; Purbajanti, Endang (Journal of Tropical Crop Science and Technology, 2020)
Banana plants are annual horticultural crops that have production capability without depending on the season and are widely cultivated in the tropic or subtropic areas. Tissue culture can produce good-quality banana seedlings in large quantities. To stimulate their metabolic systems, Banana plantlets from tissue culture require appropriate growing media and growth regulators such as auxin. The research aims to examine the effect of IAA auxin hormone concentration, the composition of sand: compost: husk charcoal and its interactions on the growth of raja bulu banana plantlets. The research was conducted in July - September 2019 at the Plant Physiology and Breeding Laboratory, Faculty of Animal and Agricultural Sciences, Diponegoro University, Semarang. The study used a complete randomized factorial design 4x2 with 5 replications. The first factor was IAA concentration (K) consists of 4 levels, K0: 0 ppm, K1: 30 ppm, K2: 60 ppm, and K3: 90 ppm. The second factor was the composition of growing media (M), M0: sand: compost: husk charcoal (1: 1: 1) and M1: sand: compost: husk charcoal (1: 1: 2). Data were analyzed by F test and proceeded by DMRT test at the level of 5%. The results showed that IAA significantly affected stem diameter, number of leaves, chlorophyll content and nitrate reductase activity of banana seedlings. The treatment of growing media significantly affected plant height and number of leaves. Concentration of 30 ppm IAA at all growing media increased significantly on stem diameter, number of leaves, chlorophyll content and nitrate reductase activity.